Wishes for christmas ebook - Michaels, Fern (2015)
The bestselling author joins two of her series—the Sisterhood and the Godmothers—for a holiday adventure to remember. This Christmas, instead of finding and punishing bad guys, all Maggie Spritzer wants is to bring a little more joy to the world—especially to a beloved teacher from her past. And as the Sisterhood unites to find her, they learn that no holiday treat is as fulfilling as giving to others . . . Meanwhile, with a little help from the other Godmothers, Toots Loudenberry is preparing for Charleston's annual holiday showcase of historic homes. But when the Godmothers sense trouble with one of the decorators, they must tackle a mystery and hope for a happy ending . . . When Sisters and Godmothers unite, the result is a warm and wonderful holiday—with a special touch of magic . . . Praise for #1 New York Times –author Fern Michaels and Her Novels "Tirelessly inventive and entertaining." — Booklist on Up Close and Personal "Fast-moving . . . entertaining . . . a roller-coaster ride of serendipitous fun." — Publishers Weekly on Mr. and Miss Anonymous "Michaels just keeps getting better and better with each book . . . She never disappoints." — RT Book Reviews on Forget Me Not